EXPLORING THE CORRELATION BETWEEN BLOOD KLOTHO AND GLYCEMIC STATUS IN DIABETIC NEPHROPATHY PATIENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Diabetic nephropathy, a common complication of diabetes, is characterized by kidney damage resulting from prolonged high blood sugar levels. Recent research has been delving into the role of klotho, a protein with potential anti-aging and renal protective properties, in diabetic nephropathy. This study aimed to investigate the correlation between blood klotho levels and glycemic status in diabetic nephropathy patients.